PISA-based assessment development in environmental issues: Fostering numeracy literacy through waste management context - R. Ramadhani; Eni Nuraeni; Widi Purwianingsih (University of Muhammadiyah Malang, 2025)
Numeracy literacy is a crucial skill for understanding, using, and communicating effectively with numbers, facts, and mathematical procedures in various real-world situations. The development of numeracy literacy is crucial because it is one of the essential prerequisites for life skills in the 21st century. This study aims to develop a valid numeracy literacy assessment test in the context of waste management. This research is Research and Development (R&D) using the ADDIE development model, which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. The developed instrument was then field-tested on 50 eleventh-grade students at a state high school in Bandung City. Data collection techniques included expert validation, instrument testing, and interviews. Data analysis utilized quantitative descriptive analysis, describing the results of expert validity calculations and instrument test data using Anates software. The research findings indicate that the developed instrument, comprising 15 questions, is valid and suitable for use, as assessed by expert validators. Additionally, the instrument pilot test results indicated that most questions had sufficient validity, high reliability, good discrimination index, and moderate difficulty levels.